Improvement of distribution transformer fault analysis using FRA method - Nasser Al-Ameri, Salem Mgammal Awadh (2019)
The distribution transformers are one of the most expensive components in the electrical power distribution system. During its lifetime, distribution transformers are exposed to several failures. For this reason, it is crucial to continuously monitor its condition. Frequency Response Analysis (FRA) is an advanced electrical test, which is commonly employed to investigate the transformer’s main winding. Moreover, it has been shown to be sensitive to non-mechanical changes such as winding insulation. The measured FRA result needs to be compared with the previous measurement to identify any variation between them. The variation will indicate mechanical changes in the transformer. However, interpreting the variation to determine the type, location, and severity of the suspected failure, requires expertise. For this reason, further understanding of the damage detecting characteristic of FRA is required. In this study, an electrical circuit model is developed based on 33/11kV, 1MVA distribution transformer to investigate the influence of various changes in the winding RLC values on the frequency response. The model is also used to simulate other failures such as winding deformation, bushing and short circuit faults. In addition, the tap changer fault and weakness of clamping structure are also investigated by examining an 11/0.433 kV, 500KVA distribution transformer. Additionally, the transformer ageing and degradation of winding’s insulation is also investigated using different FRA measurement configuration. Findings show that tap changer coking and clamping faults affect the frequency response at less than 2kHz. FRA capacitive inter-winding shows isolation in between 2kHz to 20kHz due to transformer ageing. The frequency response shifting towards lower frequencies at 20kHz to 2MHz due to winding insulation degradation. Also, in this study, the method or interpretation scheme for FRA is obtained. It is a guideline in the form of a flowchart, which is proposed for the first time and helps the engineers in having a better interpretation of FRA results. In conclusion, this study is to improve the understanding on the distribution transformers faults detection using FRA method.